A randomized clinical trial of technical modifications of appendix stump closure during laparoscopic appendectomy for uncomplicated acute appendicitis - Ihnát, Peter; Tesař, Milan; Tulinský, Lubomír; Ihnát Rudinská, Lucia; Okantey, Okaikor; Durdík, Štefan (BMC surgery, 2021)
BACKGROUND: Closure of the appendix stump presents the most critical part of laparoscopic appendectomy. The aim of the present study was to compare the medical outcomes and cost analysis of laparoscopic appendectomy with respect to the different methods of stump closure. METHODS: This was a prospective randomized clinical trial conducted in a single institution (University Hospital Ostrava) within a 2-year study period. All included patients were randomized into one of three trial arms (endoloop, hem-o-lok clips or endostapler). RESULTS: In total, 180 patients (60 patients in each arm) were enrolled into the study. The mean length of hospital stay (3.6 ± 1.7 days) was comparable in all study arms. The shortest operative time was noted in the hem-o-lok subgroup of patients (37.9 ± 12.5 min). Superficial surgical site infection was detected in 4.4% of study patients; deep surgical site infection was noted in 1.7% of the patients. The frequency of surgical site infections was comparable in all study arms (p = 0.7173). The mean direct costs of laparoscopic appendectomy were significantly the lowest in the hem-o-lok subgroup of patients. Laparoscopic appendectomy is not a profit-making procedure in our institution (mean profit of made from the study patients was-104.3 ± 579.2 Euro). Closure of the appendix stump by means of endostapler presents the most expensive and the highest loss-incurring technique (p = 0.0072). CONCLUSIONS: The present study indicates that all technical modifications of appendix stump closure are comparable with regards to postoperative complications. The stapler technique is significantly the most expensive. We concluded that hem-o-lok clips have the potential for becoming the preferred method of securing the appendix base during laparoscopic appendectomy. Trial registration NCT03750032 ( http://www.clinicaltrials.gov ).
Keywords: apendix; Appendix; apendicitida; lidé; Prospective Studies; laparoskopie; apendektomie; Appendicitis; Laparoscopy; Appendectomy; Humans; prospektivní studie